2018
DOI: 10.1088/2040-8986/aaed14
|View full text |Cite
|
Sign up to set email alerts
|

Atoms in complex twisted light

Abstract: The physics of optical vortices, also known as twisted light, is now a well-established and a growing branch of optical physics with a number of important applications and significant interdisciplinary connections. Optical vortex fields of widely varying forms and degrees of complexity can be realised in the laboratory by a host of different means. The interference between such beams with designated orbital angular momenta and optical spins (the latter is associated with wave polarisations) can be structured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 279 publications
0
116
0
Order By: Relevance
“…To date, there have been few studies of the spectroscopic application of twisted light, with work in the nascent area generally concerned with answering fundamental questions such as whether optical OAM could be involved in atomic electronic transitions [82,83]. Interestingly, a few exploratory studies on spectroscopic applications of structured light possessing OAM and optical activity have indicated that such a chiroptical effect is possible [84,85], and the same group has recently published work where recognizable chiroptical effects occur in the transmission of vortex beams though mouse brain tissue [86].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…To date, there have been few studies of the spectroscopic application of twisted light, with work in the nascent area generally concerned with answering fundamental questions such as whether optical OAM could be involved in atomic electronic transitions [82,83]. Interestingly, a few exploratory studies on spectroscopic applications of structured light possessing OAM and optical activity have indicated that such a chiroptical effect is possible [84,85], and the same group has recently published work where recognizable chiroptical effects occur in the transmission of vortex beams though mouse brain tissue [86].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Nonetheless, the same QED methods are highly amenable to application in the sphere of structured light [207], leading, for example, to the discovery that it is possible to deliver vortex photons by direct emission from suitably excited arrays [208][209][210] and so paving the way for a range of technical developments and implementations [211][212][213][214][215][216]. Whether the optical orbital angular momentum (OAM) of structured light could be transferred to the internal electronic degrees of freedom of an atom or molecule has been a well-debated topic, with highly significant implications in spectroscopy [217]. The first attempt at tackling this question utilized QED methods and determined that, for dipole transitions, the OAM of light is transferred to the mechanical motion of particles only; the lowest-order interaction required for OAM to be transferred to an electron is through E2 transitions [218].…”
Section: B Original Predictions Of Qedmentioning
confidence: 99%
“…with the corresponding quadrupole potential given by Eq. (8). In the following, we focus on the specific case of the Cs atom, which has been the subject of investigation involving its quadrupole transition (6 2 S 1/2 → 5 2 D 5/2 ).…”
Section: A Laguerre-gaussian Modesmentioning
confidence: 99%